Manufacturing of polymer composites using automated fiber placement and tape layup processes - Wan, Wysley Kin Yu (Nanyang Technological University, 2022)
Composite materials are gaining popularity in engineering applications in many fields due to their advantageous properties such as light weight and high strength to weight ratio. Traditional methods of fabricating such materials are labour intensive and are not preferred in cases of mass productions. Hence, automated fabrication methods such as the Automated Fibre Placement (AFP) method and Automated Tape Layup (ATL) method are being adopted and studied to obtain better fabrication processes of such composite materials. Such automated fabrication methods utilises robots for the fabrication process. Parameters such as roller pressure, layup speed, and temperature at the robot head could impact the quality of the composite materials fabricated. Hence, these parameters are crucial in making good quality composite structures. This project aimed to investigate the relationship between the robot parameters and the quality of the composite. Composite panels were fabricated using the AFP method with varying roller pressure of the robot. Mechanical load tests, which were the tensile tests and 3-point bending tests, were performed on the specimens to analyse the relationship between roller pressures and the quality of composite panels. Findings were obtained and discussed in this report, and recommendation on which is the best setting of roller pressure was included.